1993
DOI: 10.1007/bf01296105
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica cyst passers

Abstract: The present study was carried out to examine whether Entamoeba histolytica cyst passers suffer from any parasite-related bowel symptoms and to assess the frequency of spontaneous eradication of this infection. The study was carried out in two parts. In part I, stool samples were collected at random from 3536 individuals living in rural communities around Delhi. E. histolytica was isolated by the culture technique in 345 (9.7%) subjects. There was no increase in the prevalence rate of bowel symptoms in the cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Although a large number of infections remain asymptomatic, there are various types of symptomatic presentations ( Figure 1 ). It is traditionally said that 10% of infected cases show symptoms [ 6 ]; however, the real percentages of symptomatic patients in the diagnosed- E. histolytica infection are varied, ranging from <1% to 92% in the targeted populations, and depend on the diagnostic tools [ 19 , 20 , 21 , 22 ]. The previous report showed that the parasite can be spontaneously eradicated within a mean period of 8.6 months without any treatment [ 21 ]; therefore, the symptomatic percentage in E. histolytica -infected patients may be influenced by the timing of specific diagnostic procedures and the clinical severity of amebiasis.…”
Section: Variety Of E Histolytica Infectious Disea...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although a large number of infections remain asymptomatic, there are various types of symptomatic presentations ( Figure 1 ). It is traditionally said that 10% of infected cases show symptoms [ 6 ]; however, the real percentages of symptomatic patients in the diagnosed- E. histolytica infection are varied, ranging from <1% to 92% in the targeted populations, and depend on the diagnostic tools [ 19 , 20 , 21 , 22 ]. The previous report showed that the parasite can be spontaneously eradicated within a mean period of 8.6 months without any treatment [ 21 ]; therefore, the symptomatic percentage in E. histolytica -infected patients may be influenced by the timing of specific diagnostic procedures and the clinical severity of amebiasis.…”
Section: Variety Of E Histolytica Infectious Disea...mentioning
confidence: 99%
“…This problem may be caused by the limitation of observational parts in the colon when it is performed on via sigmoidoscopy. Certainly, in some cases, the parasite does not suffer from any parasite-related bowel complaints and can be eradicated spontaneously [ 20 ]. However, the appropriate treatment is currently warranted in all cases of infection with E. histolytica , even in asymptomatic individuals, because there a lot of personal factors influencing the transformation of the silent disease into more severe disease, such as age, pregnancy, corticosteroid, malignancy, malnutrition, and alcoholism [ 1 , 27 , 29 ].…”
Section: Variety Of E Histolytica Infectious Disea...mentioning
confidence: 99%